On the Hunt for More Benign and Biocompatible ABS - Pereira, Jorge F. B. [UNESP] (2016)
The late appearance of more environmentally friendly and biocompatible liquid-liquid extraction systems has triggered a shift in research interest toward aqueous biphasic systems (ABS), including those composed of ionic liquids (ILs). Although most ILs were originally considered as green solvents due to their negligible volatility, the release/escape of these materials into the environment from operations employing IL-water solvent systems rose several concerns. As a consequence, recent studies started to focus on finding more benign and biocompatible ILs for new biocompatible ABS (Bio-ABS) formulations. One of the most thoroughly studied Bio-ABS to date employs cholinium-based ILs combined with various polymers or high-melting inorganic salts; however, other Bio-ABS were also suggested and tested, like those utilizing amino-acid-based ILs as ABS promoters. Although naturally resourced and biodegradable ILs obviously improve the biocompatibility and sustainability of a given ABS, similar attention has to be paid to the selection of the other coexisting phase-forming agents (polymers, biopolymers, sugars, and/or biodegradable high-melting salts) in order to achieve a truly environmentally conscious system. Starting from this basis, in this chapter we (a) review and summarize the available information on Bio-ABS published so far, (b) highlight the most important differences between IL-based Bio-ABS and non-Bio-ABS, (c) show examples of nontoxic and biodegradable phase-forming agents, and (d) evaluate the applicability and future industrial perspectives of IL-based Bio-ABS.